Мировая история - Волкова А. В. (Детская энциклопедия РОСМЭН, 2013)
Экземпляры: Селтинская районная библиотека (к/х) (20140609) / Инвентарный номер: 200706 / Цена: 86.00 / Сис.шифр: 63.3(0) / Авт.знак: М 64 / ГРНТИ: 03 / ББК: 63.3(0)я2